Njoo Cheong Seng: An Artist in the Fight between Liberalism and Eastern Traditions - Dwi Susanto; Deny Tri Ardianto (Wacana Seni Journal of Arts Discourse, 2021)
As an artist, Njoo Cheong Seng (writer, playwright, film producer, and director) made efforts to respond to colonial discourse through his works and activities from the mid-1920s to the 1940s. His responses manifested in the forms of resistance and counter discourse. This paper seeks to explore the ideas and forms expressed in the counter discourse by Njoo Cheong Seng, an artist of Chinese Indonesian ethnicity. The perspective applied in this research is the postcolonial approach, particularly with regard to the concepts of hybridity and resistance. The deconstructive reading framework interpretation method was applied to determine the opposing relationship between the colonised and the coloniser discourses. The results show that Njoo Cheong Seng supported the movement to restore Chinese characteristics as a form of cultural resistance to the idea of Dutch colonial liberalism. The strategy that he used seemed to support the colonial discourse while simultaneously masking the hybridity that he promoted through ideas such as cultural nationalism. In addition, Njoo Cheong Seng and other similar collective artists developed a strategy that seemed to be of a puritan nature; however, it was, in fact, a simultaneous hybridity that consistently responded to modernity values. Njoo Cheong Seng actually opposed modernity born of liberalism. Essentially, he opposed the concept of the human as the centre of everything, or anthropocentrism.